Development of Telematics and its Application in Water Transport - Kovačević, Dražen; Maković, Branko; Kaštela, Slobodan (Promet - Traffic&Transportation)
Significant increase in traffic demand at the end of the 2nd century and the increasing anthropogenic environmental pollutionhave resulted in the need to introduce the telematics-supportedintelligent transport systems in all the traffic branches.The work presents the development and the basic characteristicsof transport systems managed by information and communicationtechnologies. Also, the possible development and advantagesof implementing telematics in the traffic along theriver of Danube through Austria, as well as monitoring sea-goingships and containers in intennodal traffic.